Public Perception of Women’s Participation in Tarung Derajat Martial Arts in Semarang City - Kiki Revalyn Amelia; Ipang Setiawan (Physical Activity Journal (PAJU), 2026)
Tarung Derajat is an indigenous Indonesian martial art that emphasizes physical strength, discipline, and character building. Although its development shows progress in terms of training and achievements, women's participation in this sport is still relatively low due to the influence of gender stereotypes and social norms that associate contact martial arts with masculinity. This study aims to describe the public perceptions of Tarung Derajat, perceptions of women's participation, as well as the role of social factors and media in shaping public acceptance. The research uses a descriptive quantitative approach with a cross-sectional survey through an online Likert-scale questionnaire. The results indicate that public perception of Tarung Derajat falls into the good category, especially regarding the values of sportsmanship, discipline, and character building, but the perception of women's participation is still lower, reflecting the influence of traditional social and cultural constructs. Social factors and the media have been proven to play an important role in shaping the level of public acceptance, thus it is necessary to have more inclusive and gender-equitable women's participation in Tarung Derajat.